SoBat Kanker smartphone application to improve oral chemotherapy adherence among cancer patients in Indonesia: Development, usability, and feasibility pilot study - Atika Wahyu Puspitasari, Susi Ari Kristina, Satibi, Yayi Suryo Prabandari (Journal of Applied Pharmaceutical Science, 2024)
This study aimed to design, develop, and evaluate the usability and feasibility of the SoBat Kanker smartphone application to improve oral chemotherapy adherence among Indonesian cancer patients. This mixed-methods study was conducted from January 2022 to April 2023 at the National Cancer Centre, Jakarta. This study was conducted in two sequential phases: Phase I focused on developing the app using a user-centred design approach and evaluating the app using a System Usability Scale (SUS), and Phase II focused on the feasibility test of the app using one group pre-post-test design. Medication adherence was measured to test the feasibility of use using the oral chemotherapy adherence scale. The SoBat Kanker app was successfully developed in Bahasa Indonesia and was available in the Google Play Store. The app features consisted of a list of patient medications and alarm reminders for taking a drug, chatting with a pharmacist, medication information, and a diary with reminders to keep appointments related to refilling prescriptions and attending the hospital. The average system usability (SUS) score was 85.33, indicating grade A and excellent system usability. Preliminary adherence outcome measure showed significant adherence improvement in pre-post intervention at 6-week follow-up (p < 0.001). Smartphone application programs may be useful and support cancer patients taking medication as prescribed. In this usability and feasibility study, the SoBat Kanker app showed acceptable, easy-to-use, and improved medication adherence. However, further studies are necessary for efficacy testing in a large-scale randomized controlled trial.
Keywords: Cancer, adherence, oral anticancer medication, smartphone application, user-center design